Milk~fat content of Jersey crosbreds under Indian village conditions - GOKHALE, S B; MANGURKAR, B R (The Indian Journal of Animal Sciences, 2013)
The data on butter-fat content of 16 101 milk samples generated form 1 614 Jersey crossbreds under rural conditions calved during 1980-1992 were analysed. The average milk-fat content was 4.195±0.152%. Least-squares (LS) analysis showed that the effect of breed, period, region, season of calving, parity and age at calving had significant effect on fat content of milk. The stage of lactation did not affect milk-fat content.The interaction between breed x season, breed x stage of lactaLion, season x stage at calving, stuge of lactationx age at calving and region x stage of lactation were all significant. The interaction effects due to season x period of calving and period x stage of lactation, however, were not significant. Halfbred Jersey crossbreds had more milk-fat content than other exotic blood levels studied. The milk produced by winter calves (4.322±0. 156) and crossbreds in their third lactation gave highest milk-fat content (4.425±0.169)'